Inclusive education and disability in Costa Rica: a perspective from public politics - Meléndez Rojas, Raudin Esteban (2018)
This essay describes some of the laws and public policies that in Latin America and especially in Costa Rica are aimed at endorsing the rights and promoting the social inclusion of people with disabilities. Emphasis is placed on inclusive education policies in Costa Rica, particularly those aimed at people with visual disabilities. From the above, it is concluded that Costa Rican laws and institutions regarding rights and policies for people with disabilities have evolved and had an impact on this vulnerable group of the population. It is reflected that, in general, a greater amount of data and information is needed, referring to people with disabilities and to the institutions that implement public policies in this area, data and information that can be more disaggregated and systematized, for a more effective evaluation of policies aimed at people with disabilities.